Response prediction of 177Lu-PSMA-617 radioligand therapy using prostate-specific antigen, chromogranin A, and lactate dehydrogenase - Rathke, Hendrik; Holland-Letz, Tim; Mier, Walter; Flechsig, Paul; Mavriopoulou, Eleni; Röhrich, Manuel; Kopka, Klaus; Hohenfellner, Markus; Giesel, Frederik L.; Haberkorn, Uwe; Kratochwil, Clemens (Journal of nuclear medicine, 2020)
Neuroendocrine-like trans-differentiation of prostate cancer adenocarcinomas correlates with serum levels of Chromogranin A (CgA) and drives treatment resistance. Aim of this work was to evaluate whether CgA could serve as a response predictor for 177Lu-PSMA617 radio-ligand therapy (PSMA-RLT) in comparison to the established tumor markers. Methods: 100 consecutive patients with metastasized castration resistant prostate cancer (mCRPC) scheduled for PSMA-RLT were evaluated for prostate specific antigen (PSA), lactate dehydrogenase (LDH) and CgA at baseline and in follow-up of PSMA-RLT. Tumor-uptake of PSMA-ligand, a known predictive marker for response, was assessed as a control-variable. Results: From the 100 evaluated patients, 35 had partial remission (PR), 16 stable disease (SD), 15 mixed response (MR) and 36 progression of disease (PD). High tumor-uptake (above salivary gland uptake) translated into PR with an Odds Ratio (OR) of 60.265 (95%-CI 5.038-720.922). Elevated LDH implied a reduced chance for partial remission with an OR of 0.094 (95%-CI 0.017 - 0.518) but increases the frequency of progressive disease (OR 2.717, 95%-CI 1.391-5.304); All patients who achieved partial remission had a normal baseline LDH. Factor-2 elevation of CgA increased the risk for progression with an OR of 3.089 (95%-CI 1.302 - 7.332). Baseline PSA showed no significant odds. Conclusion: In our cohort baseline PSA had no prognostic value for response prediction. LDH was the marker with the strongest prognostic value and elevated LDH increased the risk for progression of disease under PSMA-RLT. Elevated CgA demonstrated moderate impact as a negative prognostic marker in general but was explicitly related with the presence of liver metastases. Well in line with literature, sufficient tumor uptake is a prerequisite to achieve tumor-response.